Credible and salient: examining frame resonance through Athlete Ally - Schmidt, Samuel H.; Hancock, Meg G.; Frederick, Evan L. (Sport in society, 2023)
Scholars have noted that, within Social Movement Organizations (SMO), communication plays an important role achieving social change. One SMO, Athlete Ally, aims to end homophobia and transphobia in sport. Founded in 2011, Athlete Ally consists of less than 10 full-time members and over 150 Athlete Ambassadors. To successfully generate change within sport, Athlete Ally must maintain clear and consistent communication with its constituents Thus, the purpose of this study was to examine how Athlete Ally develops credible and salient frames throughout the organization and with its Athlete Ambassadors through the lens of Cultural Theory/Frame Analysis. The researchers interviewed employees, board members, and Athlete Ambassadors of Athlete Ally and examined organizational documents to understand how credible and salient frames are developed. Results indicated strong core values, personal stories and hard data, a diverse staff, target messaging, and sport itself were strategies employed by Athlete Ally to create frames that resonate with its audience.